Physical Fitness and Emotional Quotient Toward Soccer Referees Performance (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2018)
Physical fitness and Emotional Quotient (EQ) are important aspects for referees. This is because the distance traveled by the referees during the game is related to soccer players and psychological disorders often experienced by the referee. However, the training as an effort to refine the performance of the referees has not been done yet. Based on these facts, this study was aimed at analyzing: (1) the contribution of physical fitness to the performance of referees; (2) EQ contribution to referees' performance, and; (3) the contribution of physical fitness and EQ simultaneously and significantly to the performance of the referees. To achieve such purposes, this study used correlational descriptive method by involving 71 members of soccer referee in PSSI (Indonesia football association) association of Pekalongan and Batang Regencies as the population in this study. The population was sampled into 68 active referees. Their physical fitness data were obtained through psychomotor tests using FIFA Fitness Test guidelines. Meanwhile, EQ data were obtained through a test by using Assessing Emotions Scale guidelines. Besides, the performance referee data were obtained through the assessment done by the match supervisor using referee assessment guidelines and assistant referees applicable in PSSI. The data obtained were analyzed using path analysis and resulted the significance value of 0,05. The results showed that the performance of the referee is contributed by: (1) Fitness Test equal to 5.06%; (2) EQ equal to 15.28%; (3) Fitness Test and EQ together equal to 52%.